The evolution of resource distribution, slow diffusion, and dispersal strategies in heterogeneous populations - Zahan, Ishrat; Kamrujjaman, Md.; Abdul Alim, Md.; Shahidul Islam, Md.; Khan, Taufiquar (Frontiers in Applied Mathematics and Statistics, 2023)
Population diffusion in river-ocean ecologies and for wild animals, including birds, mainly depends on the availability of resources and habitats. This study explores the dynamics of the resource-based competition model for two interacting species in order to investigate the spatiotemporal effects in a spatially distributed heterogeneous environment with no-flux boundary conditions. The main focus of this study is on the diffusion strategy, under conditions where the carrying capacity for two competing species is considered to be unequal. The same growth function is associated with both species, but they have different migration coefficients. The stability of global coexistence and quasi-trivial equilibria are also studied under different conditions with respect to resource function and carrying capacity. Furthermore, we investigate the case of competitive exclusion for various linear combinations of resource function and carrying capacity. Additionally, we extend the study to the instance where a higher migration rate negatively impacts population growth in competition. The efficacy of the model in the cases of one- and two-dimensional space is also demonstrated through a numerical study. AMS subject classification 2010 92D25, 35K57, 35K50, 37N25, 53C35.